Melatonin for sedative withdrawal in older patients with primary insomnia: a randomized double-blind placebo-controlled trial - Lähteenmäki, Ritva (Blackwell Science Inc, 2014)
AIM: We compared the efficacy of melatonin and placebo as adjuvants in the withdrawal of patients from long term temazepam, zopiclone or zolpidem (here ‘BZD’) use. METHODS: A double-blind, placebo-controlled, randomized trial was conducted in a primary health care outpatient clinic. Ninety-two men or women (≥55 years) with primary insomnia and chronic BZD use received controlled release melatonin 2 mg (CRM) (n = 46) or placebo (n = 46) during the 1 month withdrawal from BZDs. Psychosocial support was provided. Follow-up continued for up to 6 months. Successful BZD withdrawal by the end of 1 month was confirmed by BZD plasma determinations, while reduction in BZD use and abstinence continuing for 6 months were noted. RESULTS: There were two drop-outs on CRM and one on placebo. After a 1 month withdrawal, 31 participants (67%; 95% CI 54, 81) on CRM and 39 (85%; 74, 95) on placebo had withdrawn completely (intention-to-treat analysis between groups, P = 0.051; per protocol P = 0.043). Reduction in BZD use was similar or even more rare in the CRM than in the placebo group (P = 0.052 per protocol). After 6 months, 14 participants in the CRM group and 20 in the placebo group remained non-users of BZD (NS between groups). BZD doses were higher in the CRM than in the placebo group at the end of the 6 month follow-up (P = 0.025). Withdrawal symptoms did not differ between the groups. CONCLUSIONS: Gradual dose reduction of BZDs combined with CRM or placebo, and psychosocial support produced high short term and moderate long term BZD abstinence. CRM showed no withdrawal benefit compared with placebo.